2018
DOI: 10.1111/mmi.13960
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of the regulation of Cu metabolism in Cryptococcus neoformans

Abstract: The ability of the human fungal pathogen Cryptococcus neoformans to adapt to variable copper (Cu) environments within the host is key for successful dissemination and colonization. During pulmonary infection, host alveolar macrophages compartmentalize Cu into the phagosome and C. neoformans Cu-detoxifying metallothioneins, MT1 and MT2, are required for survival of the pathogen. In contrast, during brain colonization the C. neoformans Cu importers Ctr1 and Ctr4 are required for virulence. Central for the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 103 publications
3
70
0
Order By: Relevance
“…When grown under limiting concentrations, C. albicans activate Cu utilization genes such as the Cu transporter Ctr1 while under Cu excess genes involved in Cu detoxification (Crp1) and relocalization (Atx1, Cup1, Ccc2) were induced. As in other fungi (van Bakel et al, 2005;Rustici et al, 2007;Garcia-Santamarina et al, 2018), we also found that iron utilization genes were differentially modulated by Cu depletion which might reflect a situation of iron deficiency as well. Indeed, iron uptake depends on the multicopper ferroxidases and consequently Cu deprivation engender a subordinate iron depletion in C. albicans cells.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…When grown under limiting concentrations, C. albicans activate Cu utilization genes such as the Cu transporter Ctr1 while under Cu excess genes involved in Cu detoxification (Crp1) and relocalization (Atx1, Cup1, Ccc2) were induced. As in other fungi (van Bakel et al, 2005;Rustici et al, 2007;Garcia-Santamarina et al, 2018), we also found that iron utilization genes were differentially modulated by Cu depletion which might reflect a situation of iron deficiency as well. Indeed, iron uptake depends on the multicopper ferroxidases and consequently Cu deprivation engender a subordinate iron depletion in C. albicans cells.…”
Section: Discussionsupporting
confidence: 77%
“…We also analyzed the 50 gene promoters that mac1 failed to activate for potential consensus binding motifs and identified two enriched mini-sequences one of which is the well-known Mac1 binding site (McDaniels et al, 1999;Garcia-Santamarina et al, 2018; Figure 4D). Mac1 binding motif was found in the promoters of Ctr1 and Sod3, as previously reported (Woodacre et al, 2008;Li et al, 2015), in addition to the ferric reductases Fre30 and Fre7 (Table 1).…”
Section: Mac1-mediated Control Of Copper Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedgraphs were plotted using Integrative Genomics Viewer 2.0.30 (Broad Institute). Genes were determined as differentially bound if the fold change in ChIP signal between both conditions was greater than 1.5-fold in either direction (based on [50]).…”
Section: Chip-seq Library Constructionmentioning
confidence: 99%
“…The extracellular Cu 2+ is reduced by plasma membrane reductases prior to internalization. These plasma membrane reductases are equally widespread in eukaryotes (Garcia-Santamarina et al 2018;Marvin et al 2004).…”
Section: Copper Import Across Membranesmentioning
confidence: 99%